2015
DOI: 10.1103/physreve.91.022310
|View full text |Cite
|
Sign up to set email alerts
|

Rotational dynamics of simple asymmetric molecules

Abstract: Molecular dynamic simulations were carried out on rigid diatomic molecules, which exhibit both α (structural) and β (secondary) dynamics. The relaxation scenarios range from onset behavior, in which a distinct α process emerges on cooling, to merging behavior, associated with two relaxation peaks that converge at higher temperature. These properties, as well as the manifestation of the β peak as an excess wing, depend not only on thermodynamic conditions, but also on both the symmetry of the molecule and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…It is apparent in figure 5 that the Debye model is a very good approximation for the non-associated system at room temperature. Upon cooling the system, only one primary relaxation process is detected, similarly to the results obtained for slighlty asymmetric Lennard-Jones molecules [20]. The Debye model is less satisfactory at low temperatures, and the Davidson-Cole approach, shown in figure 6, produces better results.…”
Section: Dynamic Dielectric Propertiessupporting
confidence: 60%
See 1 more Smart Citation
“…It is apparent in figure 5 that the Debye model is a very good approximation for the non-associated system at room temperature. Upon cooling the system, only one primary relaxation process is detected, similarly to the results obtained for slighlty asymmetric Lennard-Jones molecules [20]. The Debye model is less satisfactory at low temperatures, and the Davidson-Cole approach, shown in figure 6, produces better results.…”
Section: Dynamic Dielectric Propertiessupporting
confidence: 60%
“…On the other hand, the influence of temperature on the dielectric properties of the non-associated liquid at very low temperatures will also be studied. It has been previously obtained that systems composed by Lennard-Jones rigid asymmetric diatomic molecules exhibit both structural and secondary relaxation processes in rotation below an onset temperature [19,20]. We intend to check on the dielectric relaxation behaviour of a system made up by sligthly asymmetric diatomic molecules, with an added constant dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…This was done in the same way as in the 3D systems in refs. [31,32,33,34]; to wit, the energy parameters are those of the KA liquid, i.e., = = = 1.0, = = = 1.0, and = = = = 1.5. To set , we use the original KA parameters for the larger A and C particles, while the smaller B and D particles have a size 62.5% that of A and C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Model systems most often used to study glassy dynamics are mixtures of spherical particles, which do not show a JG relaxation, at least up to the timescales accessible by molecular dynamics simulations. Instead, we simulate a rigid, asymmetric dumbbell-shaped molecule, the simplest shape that captures the characteristics observed experimentally for the JG process [31,32,33,34]. The simulations were done for a two dimensional molecule, so that clustering can be more clearly depicted.…”
Section: Introductionmentioning
confidence: 99%
“…However, many experimental results have shown that some β-relaxation processes are closely related to the structural relaxation process. Very recent molecular dynamics simulation results for asymmetric diatomic molecular glass formers demonstrate that the α-relaxation process has a close relationship with a secondary relaxation process known as the Johari-Goldstein β-relaxation (J-G) process [4][5][6][7]. This type of secondary relaxation process is generally considered to be universal in nature as it appears in a variety of glass formers such as supercooled liquids, metallic glasses, polymeric glasses and plastic crystals.…”
Section: Introductionmentioning
confidence: 99%